L’émergence de l’«acteur napoléonien» au XIXe siècle - Laura O’Brien (Seminario di filologia francese, 2021)
The period after the July Revolution of 1830 in France were marked by a wave of new plays about Napoleon. The popularity of these Napoleonic plays required the emergence of actors who, very quickly, became specialists in the role. This article discusses these first great “Napoleons of the theatre”, who created what became a tradition and a metier inpopular French theatre. It shows how the role was performed in the two decades after 1830, as well as responses to the interpretations of Napoleon in this period. The article argues that, by bringing images and memories of Napoleon to life before the public, these actors helped tore shape the popular image of Napoleon, but also to transform him into a more cultural, historicised figure, rather than a political force in the contemporary present.